RET 898-901Del mutant, a variant of unknown significance, has a durable response to Pralsetinib in a Medullary Thyroid Carcinoma patient - Patrick, J. Conway; Dmytro, B. Kovalskyy; Marco, A. Alanis; Amy, L. Mumbower; Kayla, E. Chamberlin; Daruka, Mahadevan (Journal of Thyroid Cancer, 2023)
Background Patients with distant metastatic Medullary Thyroid Carcinoma (MTC) have an estimated 40% ten-year survival rate. Gain of function mutations in the REarranged during Transfection or RET gene in MTC can result in an aggressive phenotype resistant to traditional therapy. In this case report, we describe the treatment of an MTC patient with a unique RET kinase deletion mutation. Case presentation Since diagnosis, 21 years ago, this patient has had chronically elevated calcitonin levels (>40,000 pg/mL) that was unable to be controlled by conventual therapy and clinical trials. As result of uncontrolled MTC, metastatic disease was found in the spine, liver, and lungs. Circulating tumor DNA (ctDNA) analysis identified a RET 898-901Del mutation, reported as a variant of unknown significance. The treating physician identified that the deletion was in the activation loop of RET kinase and considered that the mutation was constitutively activating RET kinase. The patient was prescribed Pralsetinib, a small molecule inhibitor targeting the ATP binding site of RET. Pralsetinib treatment achieved a durable response and was able to significantly decrease serum calcitonin levels (<200 pg/mL) and tumor size. Conclusion This RET deletion mutation is a pathogenic mutation with comparable enzymatic activity to the more common RET M918T mutation. The case report highlights the versatility of structural biologic approaches to guide therapeutic decisions.
Keywords: RET; Deletion mutation; Parlsetinib; Thyroid Carcinoma